ANALISIS UNTUK MEMPREDIKSI STOK ASET DI PT. XYZ MENGGUNAKAN ALGORITMA APRIORI - Nur Ikhsan; Fahmi Arzalega; Nur Nawaningtyas Pusparini (LPPM Universitas Putera Batam, 2023)
There was an error in the staff's recording of goods and calculations, making it difficult to locate the necessary data. A collection of data that has been recorded and calculated ultimately renders the data useless. The purpose of the study was to determine whether the RapidMiner application's use of data mining can aid in stock prediction and data analysis. For stock predictions, the researcher employs the a priori algorithm approach in this instance. The findings indicate that employees will request the most support in 2022—a printer—if they request a laptop by as much as 7.9%. The laptop category will dominate in 2021, and the PC category will dominate in 2022. Therefore, the highest level of confidence for 2022 is that employees will request a printer if they request a PC and an external hard disk of 100%. The conclusion states that employees can use the RapidMiner application to perform data mining by applying the a priori algorithm, which aids in data analysis and predicts employee supply requirements.